2019
DOI: 10.1002/prep.201800382
|View full text |Cite
|
Sign up to set email alerts
|

Fragment Velocity Characteristics of Warheads with a Hollow Core under Asymmetrical Initiation

Abstract: Fragment velocity characteristics of warheads are key issues in the field of explosion technology and protection. However, the fragment velocity characteristics of a warhead with a hollow core under asymmetrical initiation are rarely touched. In this work, the effects of the diameter of the hollow core on the fragment velocities of warheads under asymmetrical initiation were investigated by experimentally verified numerical simulations. The results showed that the fragment velocity‐time curves exhibited a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The velocity enhancement mechanism of an asymmetrically two lines warhead was due to the detonation distance and the pressure increase in the Mach wave. An et al [29] investigated the fragment acceleration of amiable warheads due to the collision of the detonation wave. They adopted the increase in hollow-core diameter to enhance the efficiency of detonation wave collision in a large-shaped charge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The velocity enhancement mechanism of an asymmetrically two lines warhead was due to the detonation distance and the pressure increase in the Mach wave. An et al [29] investigated the fragment acceleration of amiable warheads due to the collision of the detonation wave. They adopted the increase in hollow-core diameter to enhance the efficiency of detonation wave collision in a large-shaped charge.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the irregular or Mach reflection of detonation waves, and most of their works focused on their application in fragment driving and explosively formed projectile (EFP) formation [28,29,31]. The effect of detonation wave collisions on metal rods has received minimal attention.…”
Section: Introductionmentioning
confidence: 99%
“…Results confirm that the formula developed with a numerical model could accurately predict fragment speed dispersion along the axis and circumference of the cylindrical skin under an eccentric start point at one end, thereby simulating the edge effect. Further, Studies reported calculating the fragment velocity of hollow-core warheads with asymmetric detonation [31][32][33][34] . Recently, Jifeng Wei et.al 35 studied the fragmentation of a thinwalled Q235 steel shell under an explosion of TNT.…”
Section: Introductionmentioning
confidence: 99%
“…An et al [5] and Felix et al [6] studied fragment axialspeed distribution characteristics for various explosions. König [7] and Huang et al [8] studied a formula for the fragment dispersion angle of cylindrical warheads with end effects by experimental testing and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%